Peculiarities of legal regulation and improvement of the social protection policy of the low income families in Ukraine - Farion-Melnyk, Antonina; Melnyk, Yurii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
In the article, the author examined the specific features of defining the legal status of a low-income family which lives on the territory of Ukraine in accordance with the current legislation, and also characterizes the reasons which lead to an increasing number of such families every day – rising prices for essential goods, reduction of the number of jobs due to bankruptcies, reorganization or re-profiling of business entities, reduction of production, deterioration of the economic situation in general; this is also facilitated by a significant gap between the living standards of the established groups of families. The article identifies the essence and role of the state social assistance in ensuring the stable functioning and development of families, as well as its forms and methods of delivery. The insecurity of low-income families in Ukraine requires a review of the system of social assistance and a comprehensive study of its theoretical and legal principles. The author established in which cases a family is allowed to apply to the Department of Labor and Social Protection of the Population to provide the necessary documents and receive social assistance allocated by the State to low-income families. The author also analyzed the size of the subsistence minimum as the main criterion for determining the need to provide assistance to families who have submitted a package of documents. The reasons and criteria for which state social assistance is not granted were highlighted. Based on the results of the study, the author has made a number of proposals to improve the legal regulation of problems related to improving the social status of low-income families and to resolve contradictions in the social assistance policy. The author proposed to systematize and unify the legal document to regulate all types of assistance to low-income families, the procedure for their appointment and payment. Proposals have been made to improve the system for assessing the social status of families in order to establish their eligibility for social assistance, as well as to simplify the mechanism for its receipt. On the basis of the study, a number of recommendations have been made for the development of programs for social development and support of low-income families in Ukraine.